Free Vibration Analysis of Composite Cylindrical Shell Reinforced with Silicon Nano-Particles: Analytical and FEM Approach - Jweeg, Muhsin J.; Njim, Emad K.; Abdullah, Orhan S.; Al-Shammari, Mohsin A.; Al-Waily, Muhannad; Bakhy, Sadeq H. (Physics and Chemistry of Solid State, 2023)
Previous research presented the effect of nanomaterials on the mechanical properties of composite materials with various volume fraction effects; in addition, their research presented the effect of nanomaterials on the same mechanical characteristics for a composite plate structure, such as vibration and thermal buckling behavior. Therefore, since the use of shell structures is for large applications, it is necessary to investigate the modification of the vibration characteristics of its design with the effect of nanomaterials and study the influence of other reinforced nanoparticle types on its features. Therefore, in this work, silicon nanoparticles were selected to investigate their effect on the vibration behavior of a shell structure. As a result, this work included studying the vibration behavior by testing the shell structure with a vibration test machine. In addition, after manufacturing the composite material shell with various silicon volume fractions, the mechanical properties were evaluated. In addition, the finite element technique with the Ansys program was used to assess and compare the vibration behavior of the shell structure using the numerical technique. The comparison of the results gave an acceptable percentage error not exceeding 10.93%. Finally, the results evaluated showed that the modification with silicon nanomaterials gave very good results since the nanomaterials improved about 65% of the shell's mechanical properties and vibration characteristics.